IVF Technologies and Infertility Current Practices and New Perspectives - Vladimirov, Iavor K. (IntechOpen, 2023)
The development of science and technology in recent decades has enabled IVF methods to occupy a leading place in the treatment of infertility. This book introduces some modern infertility treatment methods that are part of IVF technologies, focusing on clinical practice. Topics discussed include semen analysis, ovarian stimulation, and basic methods applied in the IVF laboratory. The book also addresses diagnostics and treatment of the immunological factor of infertility as well as the relationship between infertility and reproductive age. This book will increase readers' knowledge and understanding of the treatment of infertility using in vitro technologies.